2023
DOI: 10.3390/galaxies11010019
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Compact Star Populations and Some of Its Open Problems

Abstract: The study of compact object populations has come a long way since the determination of the mass of the Hulse–Taylor pulsar, and we now count on more than 150 known Galactic neutron stars and black hole masses, as well as another 180 objects from binary mergers detected from gravitational-waves by the Ligo–Virgo–KAGRA Collaboration. With a growing understanding of the variety of systems that host these objects, their formation, evolution and frequency, we are now in a position to evaluate the statistical nature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 192 publications
0
0
0
Order By: Relevance
“…The discrepancy between the two approaches we treat in this work revealed that it is necessary to be careful when making assumptions over i, since different hypotheses over this quantity can lead to drastically different pulsar masses, consequently influencing the m max determination. An ideal approach would involve implementing the "accuracydependent" model while accounting for the distribution of i for each particular system, constrained from observational data, as performed for the case of black hole masses in [62], where each object was analyzed individually and it was checked that the different Keplerian parameter values employed in each mass estimate did not rely on inconsistent assumptions. A similar treatment for NS masses remains a subject for future work.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between the two approaches we treat in this work revealed that it is necessary to be careful when making assumptions over i, since different hypotheses over this quantity can lead to drastically different pulsar masses, consequently influencing the m max determination. An ideal approach would involve implementing the "accuracydependent" model while accounting for the distribution of i for each particular system, constrained from observational data, as performed for the case of black hole masses in [62], where each object was analyzed individually and it was checked that the different Keplerian parameter values employed in each mass estimate did not rely on inconsistent assumptions. A similar treatment for NS masses remains a subject for future work.…”
Section: Discussionmentioning
confidence: 99%